(untitled) (The International Journal for Scientific Research, 2025)
The focus of this research revolves around analyzing women’s issues and gender representations in the female "Jorrad" songs at weddings in the rural area of Lataifa in Sfax. It examines how oral folk literature is employed as a mirror reflecting the reality and concerns of rural women in a conservative society. Through analyzing the content of these songs, a discursive contradiction emerges between reinforcing traditional conservative values on one hand, and expressing women’s aspirations on the other. While the songs glorify the image of the obedient wife and the dominant husband, they also carry cautionary messages urging him to respect his wife and grant her the status she deserves. The study also reveals women’s suffering from symbolic violence, particularly in being deprived of the freedom to choose their life partner, as the "Jorrad" texts show women insisting on their right to marry with their consent. Despite the lack of an explicit demand for full equality, these songs constitute a committed art form that highlights pressing women’s issues, making them a living cultural medium that records the contradictions of social reality and calls for a re-examination of prevailing gender roles.